PERlLAKU HIDUP BERSIH DAN SEHAT PADA TATANAN RUMAH TANGGA DAN KEJADIAN PENYAKIT DIARE - Fajar Rahmadani S; Sri Mardojo; Imam Thohari (GEMA LINGKUNGAN KESEHATAN, 2015)
Diarrhea remains a major health problem in Surabaya. Based on data from Surabaya City Health Service in2012 there were 92,072 cases of diarrhea, and the village of Wonokusumo contributed 255 cases in 2012 andmore than doubled, as many as 608 cases in 2013.This study aims to describe the practice of PHBSin the household setting and the incidence of diarrhea. Thisis a non-experimental study using descriptive data analyses. The instrument used in gathering data was aquestionnaire and observation sheet.Results of of the study with regard to knowledge, attitudes, and practice and implementation of PHBSprinciples by housewives. In the case-group, with regard to knowledge aspect, the accomplishment wereqood or 38.4%, moderate or 44.2%, and poor or 17.4%, while the non case-group has differentaccomplishment, good or 15.1%, moderate or 61.6%. and poor or 23.3%.Results with regard to attitude among the respondents in the case group was good 19.2%, moderate 46.2%,and poor 17.3%, while in the non case-group the results were good 39.5%, moderate 54.7%, and poor5.8%. Results for practices in case group were good 18.6%, moderate 73.3%, and poor 8.1%, while in noncase group the results were good 7%, moderate 77.9%, and poor 15.1%. Finally, with regard to theapplication of PHBSprincuples, the case-group were mostly unhealthy (74.4%), whereas in the non-casegroup the most common response was healthy (65.1%).Analyses of the above data indicated that in terms of knowledge, attitude, and practice, most housewivesresponded a moderate value. Interms of PHBSimplementation the case-group showed unhealthy responsethan the non-case group.By observing the 10 indicators of good household PHBSthe family will be protected from diseasesespeciallydiarrhea